Recurrent implantation failure is associated with increased levels of fetuin-A/alpha2-Heremans-Schmid-glycoprotein. (May 2020) - Ozgu-Erdinc, A. Seval; Oskovi-Kaplan, Z. Asli; Engin-Ustun, Yaprak; Kiyak Caglayan, Emel; Yilmaz, Saynur; Yilmaz, Nafiye; Gocmen, Ayşe Yeşim; Erkaya, Salim; Delibas, Namık
Abstract: Objective: Recurrent implantation failure is defined as the absence of implantation, after two or three consecutive cycles of in-vitro fertilization (IVF), intracytoplasmic sperm injection or frozen embryo replacement. Human fetuin-A/alpha2-Heremans-Schmid-glycoprotein is a plasma protein secreted by the liver that modulates insulin action in adipocytes. Increased fetuin-A promotes adipocyte dysfunction which results in decreased adiponectin and increased fatty acids and inflammatory cytokines. Fatty acids and inflammatory cytokines were previously reported in implantation failure. Also, fetuin-A inhibits receptor tyrosine kinase activity in trophoblast growth factors which decrease trophoblast viability and invasion. In this study, we aimed to find the association between fetuin-A and implantation failure. Study design: A total of 78 women were included in this case-control study. Serum fetuin-A concentrations were measured in 42 women with recurrent IVF failure and 36 healthy women with regular cycles. Results: The mean serum fetuin-A levels of implantation failure and control women were 257.77 ± 32.18 and 219.59 ± 48.86 respectively with a p-value <0.001 (independent samples t -test). Our results showed a statistically significant difference between serum fetuin-A levels of implantation failure women and controls. Conclusion: So far reasons for implantation failure are only partially understood. The current study reveals the association between implantation failure and fetuin-A. Further studies with large population sizes are needed to investigate whether fetuin-A can be used as a marker before controlled ovarian stimulation began or regulation of fetuin-A levels with treatment or lifestyle interventions can improve implantation success.